Local revenue generation system: Its contribution to the development of the Municipality of Bacolod, Lanao del Norte - Ozarraga, Louvill (Technium Social Sciences Journal, 2022)
This study was designed to ascertain the concept of revenue generation system of Bacolod, Lanao del Norte, through the completely enumerated elected officials and permanent employees sample respondents. The pertinent data were obtained through the use of a structured questionnaire and with the help of key informants. The study utilized a cross-sectional survey design to analyze and interpret the data using frequency counts, percentage distributions, and a weighted mean. For the major findings, the local revenue generation of the municipality has increased by roughly 73.52% from 2016 to 2018. Administrative activities help the municipality cope with development, namely the issuance of ordinances, personnel augmentation, and collection strategies. Moreover, respondents were undecided about whether revenue generation contributed to infrastructure and purchases of assets. The majority of the respondents agreed that the municipality’s local revenue generation contributes to the social welfare of its constituents. However, the respondents disagreed that locally generated revenue augments the 20% development fund. The study revealed that there is a big difference between the 2018 and 2020 Real Property Tax (RPT) collection. No committee was created to monitor and supervise the municipal revenue generation system. The municipality, through its partnership with TESDA, provides skilled-job opportunities to its constituents and participants.